The high andean Cordillera of Central Argentina and chile along the Piuquenes pass-cordon del Portillo transect: Darwin's pioneering observations compared with modern Geology - Giambiagi, L. (2009)
The geological observations made by Darwin in 1835 during his crossing of the Andes from Santiago to Mendoza via the Piuquenes Pass and Cordón del Portillo are compared with the present geological knowledge of the Cordillera Principal and Cordillera Frontal at 33°-34°S. The analysis of the complex stratigraphy of the Cordillera Principal, the imbricated structure of the Aconcagua fold and thrust belt, as well as the stratigraphy and structure of the inter mountain foreland Tunuyán Basin, allows to assess the pioneer observations of Darwin. He recognized the old metamorphic basement and the granitoids and volcanic sequences of late Paleozoic to Triassic age of the Cordillera Frontal, established the Cretaceous age of the marine successions cropping out along the eastern Cordillera Principal and studied the conglomeratic deposits associated with the uplift of the Cordillera in the Alto Tunuyán Basin. Based on the study of clast provenance of the synorogenic deposits of the Alto Tunuyán Basin, Darwin recognized that the Cordillera Frontal was uplifted later than the Cordillera Principal. The present knowledge of this sector of the Andean Cordillera confirms his pioneer observations and show that Darwin was one of the first scientists ever in realizing that in an orogenic system the sequence of uplift and deformation proceeds from hinterland towards foreland, according to a process that is exceptionally well-illustrated along the Piuquenes-Cordón del Portillo transect.